CALIBRATION OF A REFLECTANCE FTIR METHOD FOR DETERMINATION OF DISSOLVED CO2 CONCENTRATION IN RHYOLITIC GLASSES - Moore G.; Chizmeshya A.; McMillan P.F. (My University, 2000)
A technique based upon infrared reflectance spectroscopy is developed as an alternative to the Fourier transform infrared (FTIR) transmission method for the quantitative measurement of dissolved molecular carbon dioxide in aluminosilicate glasses. The technique has the advantage that only a single sample surface need be polished, and no thickness measurement is necessary. The reflectance spectrum is analyzed by Kramers-Kronig relations or classical oscillator analysis to yield the optical constants and the absorption coefficient at 2350 cm-1, due to the asymmetric stretching (ν3) vibration of molecular CO2. The value obtained is in excellent agreement with values obtained by the transmission FTIR technique for a suite of rhyolitic glasses. For practical application of the method to rhyolites, an empirical correlation is developed between the normalized change in reflectance at 2350 cm-1 and the CO2 content, up to ~0.40 wt%.